Geographic variation in select species of the bat genus Platyrrhinus - Velazco, Paul M.; Ly, Grace; McAllister, Julia; Esquivel, Diego A. (THERYA, 2023)
The taxonomy of Neotropical bats is constantly changing, with new species being described and junior synonyms elevated, while other taxa are relegated to junior synonyms or subspecies. The genus Platyrrhinus has followed this trend, with some issues persisting about the current status of its subspecies. Here we evaluate variation in cranial shape and size based on geometric morphometric analyses of Platyrrhinus dorsalis and P. umbratus. P. dorsalis occurs at elevations from sea level to above 2,000 m and is found from southern Panama southward into Colombia and along both slopes of the Andes in Ecuador. P. umbratus occurs at elevations from 400 m to above 3,150 m in the Andean from Colombia south through Bolivia and Caribbean Mountain systems of Venezuela and Colombia. Our analyses did not support the recognition of subspecies in either species. The difference in skull size and shape between populations of P. dorsalis is associated with elevation, suggesting that this species exhibits an altitudinal clinal variation, with individuals being larger in the lower elevation and smaller in higher elevations. In P. umbratus the difference in skull size and shape between populations is associated with a latitudinal cline, with individuals tending to be larger in the northern part of their range. Our analyses did not reveal the existence of secondary sexual variation in P. dorsalis nor in P. umbratus.